2010
DOI: 10.1140/epja/i2010-11033-x
|View full text |Cite
|
Sign up to set email alerts
|

On the background in the $ \gamma$p $ \rightarrow$ $ \omega$($ \pi^{0}_{}$ $ \gamma$)p reaction and mixed event simulation

Abstract: Abstract. In this paper we evaluate sources of background for the γp → ωp, with the ω detected through its π 0 γ decay channel, to compare with the experiment carried out at ELSA. We find background from γp → π 0 π 0 p followed by decay of a π 0 into two γ, recombining one π 0 and one γ, and from the γp → π 0 ηp reaction with subsequent decay of the η into two photons. This background accounts for the data at π 0 γ invariant masses beyond 700 MeV, but strength is missing at lower invariant masses which was att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Before the final conclusions of [18], it was also hoped that the use of the successful mixed events method to separate the background from the signal should be sufficient to isolate the ω signal [22]. However, a simulation of the reaction [24] showed that the mixed event method produced a background essentially independent of the real background in the region of relevance to omega production, basically determined from events occurring at much lower invariant masses.…”
Section: Introductionmentioning
confidence: 99%
“…Before the final conclusions of [18], it was also hoped that the use of the successful mixed events method to separate the background from the signal should be sufficient to isolate the ω signal [22]. However, a simulation of the reaction [24] showed that the mixed event method produced a background essentially independent of the real background in the region of relevance to omega production, basically determined from events occurring at much lower invariant masses.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [12] M. Kaskulov, the part-time postdoc in the present project, showed that the mass-shift signal depended strongly on the background subtraction method. This was also realized by the CBELSA/TAPS collaboration when a reanalysis of the data and the background determination became available [13].…”
Section: Development Of the Projectmentioning
confidence: 71%
“…Simultaneously, the possibility that some signal reported in [26,27] could indicate the formation of a ω meson bound state in nuclei was ruled out, showing that the double hump structure observed in the experiment was due to uncorrelated π 0 γ production events together with the ω production and subsequent π 0 γ decay, which scaled differently with growing nuclear mass [28]. The expectations that the use of the mixed events method to separate the background from the signal could solve the problem [29] were also shown unproductive in [30], due to the fast exponential fall of the mass distribution which made inapplicable this otherwise successful tool.…”
Section: Introductionmentioning
confidence: 95%
“…The expectations that the use of the mixed events method to separate the background from the signal could solve the problem [29] were also shown unproductive in [30], due to the fast exponential fall of the mass distribution which made inapplicable this otherwise successful tool.…”
Section: Introductionmentioning
confidence: 99%